Website-based balanced nutritional education and its effect on knowledge and perception among early adolescents: a health belief model approach - Yusta Cindy Claresta; Tri Siswati; Joseph Fernando Lim; Esthy Rahman Asih; Jutharat Attawet (Berita Kedokteran Masyarakat, 2026)
Purpose: This study examined the effectiveness of a website-based balanced nutrition education program grounded in the Health Belief Model on the knowledge and perceptions of early adolescents, comparing it with conventional educational media. Methods: This quasi-experimental, pre- test-posttest control group study was conducted in Sleman, Yogyakarta (February–May 2025). Junior high school students from SMPN 1 Mlati received the website-based nutrition intervention (three 30-minute sessions on days 1, 3, and 5), while those from SMPN 1 Seyegan served as the control group (conventional/printed media). Knowledge and perceptions were assessed using structured questionnaires before and after the intervention. Data were analyzed to evaluate within- and between- group changes. Results: Both groups showed a significant increase in knowledge scores after the intervention (intervention: 39.90 to 48.43, Δ=8.53, p<0.001; control: 37.00 to 45.44, Δ=8.44, p<0.001). Perception scores also increased significantly in both groups (intervention: 48.28 to 52.27, Δ=3.99, p<0.001; control: 50.75 to 52.03, Δ=1.28, p=0.032). However, between-group analysis indicated no significant difference in knowledge improvement (p=0.911), whereas perception improvement was significantly greater in the intervention group (p=0.004). This finding suggests that website-based nutrition education serves as a more effective "cue to action" for fostering positive perceptions of balanced nutrition than conventional media. Conclusion: Website-based balanced nutrition education is more effective at shaping students' perceptions than conventional media and holds potential as a theory-based school health promotion strategy.